PERSONAL BRANDING MAHASISWA ILMU KOMUNIKASI UIN RADEN FATAH PALEMBANG DI INSTAGRAM DALAM MEMBANGUN CITRA UNGGUL SIAP KERJA - Sinta Nabillah; Putri Citra Hati; Taufik Akhyar (Konvergensi, 2026)
This study aims to understand personal branding practices carried out by Communication Science students of FISIP UIN Raden Fatah Palembang class of 2022 in constructing digital identity as part of their preparation for entering the professional world. This research employs a qualitative approach with data collection techniques consisting of in-depth interviews and documentation of activities and content displayed on students’ Instagram accounts. The findings indicate that personal branding is conducted consciously and strategically through the management of account appearance and the selection of content highlighting academic activities, organizational experiences, and communication skills relevant to their academic background. Students tend to limit personal aspects that do not support a positive image and position their main accounts as curated spaces for representing academic and professional identities. These findings demonstrate that personal branding is understood as a continuous process of building a credible, consistent, and strategic self-image in the digital space.